1996
DOI: 10.1126/science.271.5253.1278
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Presentation and T Cell Development in H2-M-Deficient Mice

Abstract: HLA-DM (DM) facilitates peptide loading of major histocompatibility complex class II molecules in human cell lines. Mice lacking functional H2-M, the mouse equivalent of DM, have normal amounts of class II molecules at the cell surface, but most of these are associated with invariant chain-derived CLIP peptides. These mice contain large numbers of CD4+ T cells, which is indicative of positive selection in the thymus. Their CD4+ cells were unresponsive to self H2-M-deficient antigen-presenting cells (APCs) but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
192
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(204 citation statements)
references
References 27 publications
11
192
1
Order By: Relevance
“…Selective loss of class II conformational epitopes in human somatic variants (38) and mice lacking DM function (23,24,39) closely correlates with CLIP occupancy. In contrast, considerable evidence suggests DM activities are nonessential for conformational maturation of other class II allelic products, but there are also contradictory results in the literature (18 -21, 30).…”
Section: Partially Disrupted Class II Conformational Maturationmentioning
confidence: 99%
See 3 more Smart Citations
“…Selective loss of class II conformational epitopes in human somatic variants (38) and mice lacking DM function (23,24,39) closely correlates with CLIP occupancy. In contrast, considerable evidence suggests DM activities are nonessential for conformational maturation of other class II allelic products, but there are also contradictory results in the literature (18 -21, 30).…”
Section: Partially Disrupted Class II Conformational Maturationmentioning
confidence: 99%
“…The class II chain specificities (36,37) and Ii chain influences affecting expression of these conformational epitopes (10,34) have been extensively discussed. Rabbit antisera specific for determinants located in the cytoplasmic tails of the ␣-and ␤-chains were generously provided by Ronald N. Germain (YFMYSKLRVQKSTWERG), bacteriophage repressor cI peptide P [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (LEDARRLKAIYEKKK), SWM 129 -153 GAMNKALELFRKDI-AAKYKELGYQG, the truncated variant of moth cytochrome 88 -103 previously described as DASP KKANELIAYLKQATK, the Ii chain 85-101 KPVSQMRMATPLLMRPM peptides, and biotin-conjugated variants were purchased from Quality Controlled Biochemicals (Hopkinton, MA).…”
Section: Abs and Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although crystallographic studies have not found any evidence for this possibility (58,60), studies with conformation-dependent Abs have suggested that peptide binding can affect the conformation of MHC class I (61, 62) and class II (43,44,59,(63)(64)(65) molecules and that such subtly altered conformations can affect recognition by TCRs (57,(65)(66)(67). Our observation that none of the hybrids reactive with A b EpIi Ϫ cells recognized H2-DM-deficient cells, and vice versa (Table I), is consistent with this idea.…”
Section: Peptide-dependence Of Alloreactive T Cell Responsesmentioning
confidence: 99%